Morningness orientation is an important determinant to circadian misalignment and tolerance: an Asian perspective. (2nd January 2020) - Majumdar, Piya; Sahu, Subhashis
ABSTRACT: Diurnal preferences refers to one's preference of performing timely activities where one may prefer for late timings and the other for earlier, which account for their chronotype that is controlled partly by genetic factors and are also influenced by environmental factors. Individual's circadian preference can be drawn using questionnaire tools as well as can be externally validated by studying various physiological parameters that has a rhythmicity. Determination of chronotype is well studied worldwide but mostly in European and American countries. Asia being the largest continent, comprising so many countries still did not have widespread studies over chronotype assessment and its implications. This review aims at jotting down the available literature regarding the chronotype evaluation and the various contributing factors in Asian perspectives such that there can be huge cross-cultural studies emphasizing environmental, geographical differences, lifestyle habits, work schedule, and other contributing factors regarding the understanding of circadian preference of humans, which is really hard to define. The dearth in studies regarding diurnal preferences and physiological altercations, which is in turn influenced by the work schedule and the resultant sleep-wake pattern disorientation, needs further investigation worldwide and this available literature may put some light in the path of future research scope.